The Flourishing Scale: Psychometric Properties in Breast Cancer Patients. - Cerezo-Guzmán, María Victoria; Soria-Reyes, Lorena M.; Alarcón-Postigo, Rafael; Blanca-Mena, María José (SAGE, 2024)
Background/Objective. Promoting well-being is a key goal of cancer care, and it needs to be assessed using appropriate instruments. Flourishing is considered part of psychological well-being and it is commonly assessed with the Flourishing Scale (FS). To our knowledge, no studies have analyzed the psychometric properties of the FS in breast cancer patients. Our aim here was to provide validity evidence for use of the FS in this context. Method. Participants were 217 Spanish women with breast cancer who completed the FS and other scales assessing positive psychology constructs and indicators of psychological maladjustment. The internal structure of the FS was analyzed using confirmatory factor analysis (CFA). We calculated the average variance extracted (AVE) to evaluate convergent validity, and both McDonald's omega and Cronbach’s alpha coefficients to estimate reliability. Item analysis was performed by computing corrected item-total correlations. Validity evidence based on relationships with other variables was obtained through Pearson correlation analysis, controlling for age and cancer stage. Results. The CFA supported a single-factor structure, with adequate goodness-of-fit indices (CFI = .997, NNFI = .996, RMSEA = .069, and SRMR = .047) and standardized factor loadings ranging from .70 to .87. The value of the AVE was .63, and the reliability coefficient obtained with both procedures was .91. Corrected item-total correlations ranged from .62 to .78. Correlation analysis showed direct and strong associations between the FS score and scores on positive psychology constructs (range from .43 to .74). The FS score was inversely correlated with scores on depression, anxiety, stress, negative affect, and pessimism (range from -.14 to -.52). Discussion. The FS is a useful tool for exploring well-being in the breast cancer context, providing useful information for psychological assessment.
Keywords: Mamas - Cáncer - Aspectos psicológicos; Mujeres - Enfermedades - Aspectos psicológicos; Flourishing; Well-being; Eudaimonic well-being; Psycho-oncology; Mental health